2021
DOI: 10.1002/cb.2006
|View full text |Cite
|
Sign up to set email alerts
|

Using the Dirichlet model to predict how fashion brands compete and grow on eBay

Abstract: E-fashion brand competition has historically been studied from an attitudinal lens, through surveys and theory-based approaches. These studies generally examine consumer attitudes, satisfaction and loyalty; highlighting that trust, satisfaction and reputation are key e-commerce success elements. However, the empirical consumer behaviour literature rebuts the use of attitudes to explain brand performance, criticising their subjectivity and the overall ineffectiveness of loyalty as a brand growth tool. The artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 94 publications
(138 reference statements)
1
5
0
Order By: Relevance
“…Our data shows that penetration predicts market share in all circumstances compared to the average purchase frequency or average spend per purchase. This is consistent with Ehrenberg et al (1990), Sharp (2010), Jung et al (2016), Martin et al (2020), or Chowdhury et al (2022) to name just a few.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data shows that penetration predicts market share in all circumstances compared to the average purchase frequency or average spend per purchase. This is consistent with Ehrenberg et al (1990), Sharp (2010), Jung et al (2016), Martin et al (2020), or Chowdhury et al (2022) to name just a few.…”
Section: Discussionsupporting
confidence: 83%
“…Later, a similar pattern was found in the purchase behaviour of consumer goods with appropriate adjustment, where familiarity has been replaced by purchase in a given period and likability by brand loyalty (Ehrenberg, 1972;Martin, 1973). Since then it has been proven to generalize across a wide range of consumption situations (packaged goods, durables, fashion, services, television viewing, websites, political polls, sports and physical activities), markets (B2B and B2C) and countries (Ehrenberg et al, 1990;Danaher et al, 2003;Yang et al, 2005;Doyle et al, 2013;Habel and Lockshin, 2013;Romaniuk and Sharp, 2015;Gruneklee et al, 2016;Jung et al, 2016;Kooyman and Wright, 2017;Taneja, 2020;Chowdhury et al, 2022). Trinh et al (2019) even found the pattern in the wine selection by its country of origin.…”
Section: Double Jeopardymentioning
confidence: 99%
“…Our classifications allow the grouping of the many self‐classified genres into meta genres (e.g., pirate metal, Viking metal, and at least a dozen more into Metal) and shape the questionnaire for our data collection. Within the DoP literature, using predefined categories, for example, ‘bread and bagels’ from Nielsen Kilts Centre for Marketing (Grasby et al, 2022) or ‘fashion clothing’ from Kantar World Panel UK (Chowdhury et al, 2021), is the norm.…”
Section: Methodsmentioning
confidence: 99%
“…While many sub‐genres appear to be self‐evident, containing terms that make it clear that Pirate Metal and Viking Metal are both parts of the Metal genre, this is not always the case. Defining a market is not inconsequential or uncontroversial but frequently occurs for items people buy (Chowdhury et al, 2021; Grasby et al, 2022) and music people listen to (Rentfrow & Gosling, 2003, 2006). However, as a genre becomes increasingly obscure, it is also listened to by a smaller proportion of the sample, so its precise location in a classification framework becomes less of an issue.…”
Section: Limitations and Future Research Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation